The Optimization of Natural Gas Utilization Network in Single Region Using Pinch Analysis Method - Anugraha, Rendra Panca; Annasit; Altway, Ali; Juwari; Renanto (ASEAN Journal of Chemical Engineering, 2020)
Natural gas is one of the cleanest energy resources and may have potency to replace crude oil as main energy resource in several decades. There are some aspects which must be concern in the development of the natural gas industry including processing, storing, distributing and utilizing of the natural gas. The network of natural gas supply also should be generated to obtain the maximum natural gas recovery. However, it is difficult to determine the most suitable network system to connect the supply and demand of natural gas due to their different time scale, flowrate and capacity. There are some studies which investigating the network system to connect the supply and demand of natural gas but there are no systematical method in determination of the optimum natural gas network in single region supply-chain using pinch analysis. Therefore, in this study, a systematical method was developed to design natural gas network system in single region (East Java) using pinch analysis. The concept of natural gas cascade calculation was introduced. The heuristics of natural gas pairing between source and sink streams in grid diagram analysis was developed. Using 0-year time minimum difference give the amount of unutilized supply with value of 258.4 billion standard cubic feet (BCF) while 3-year time minimum difference give the amount of alternative and unutilized supply with value of 639.3 BCF and 897.7 BCF, respectively. The grid diagram heuristics developed in this study gives same results with the cascade calculation result.